Determinants of medical tourism considering a geographical model: a case study of Iran - Ali Faridi Masouleh; Keramatollah Ziari; Mohammadreza Rezvani; Javad Etaat; Mohammad Amin Khorasani; Abolfazl Gilani (Social Determinants of Health, 2022)
Background: Medical Tourism has received significant attention worldwide as the most remarkable phenomenon in the tourism industry. Medical Tourism was considered a medical tourist’s behavior concerning the push/pull factors and three fundamental flows to assess the BTD model (Birthplace-Transportation-Destination). The present study aimed to unearth determinable factors of medical tourism based on a geographical model named BTD in Iran.